EVALUASI STRATEGI OPERASIONAL PENEMPATAN PASUKAN DALAM MENGATASI KONFLIK DOMESTIK: PENDEKATAN MILITER DAN POLISI - Sarjito, Aris (PPM Sdirjianbang Akademi Militer, 2025)
Abstract The purpose of this research is to analyze the effectiveness of operational strategies employed by the military and police in managing domestic conflicts. Using a qualitative approach with secondary data analysis, this study examines various case studies to understand the impact of these strategies in different socio-political contexts. The findings indicate that the police are more effective in handling small-scale social conflicts through community-based approaches, while the military is essential in responding to large-scale threats such as terrorism or separatism. However, prolonged military involvement in domestic security often leads to distrust and human rights concerns. The study recommends optimizing the role of the police in preventive security measures, defining clear limitations on military engagement in domestic affairs, and improving coordination between both institutions. Future researchers are encouraged to explore the role of technology and artificial intelligence in enhancing security strategies while ensuring compliance with human rights principles. Keywords: domestic conflict, human rights, military strategy, police operations, security policy